(untitled) (Latakia University Journal -Basic Sciences Series, 2022)
In this research, we found the integral Cauchy – Pompeiu’s formula in the octal of unit disk of the complex plain, for the continus functions class ,by editing the Cauchy – Pompeiu’s representation in the unit disk, using the reflection method, to determine the Integral’s Cauchy – Pompeiu’s Operator, in this domain, the integral Cauchy – Pompeiu’s formula in a domain ,separated onto two integrals, the first is on the boundary of the domain D ,and represents an analytic function on D, the second is on the domain , and represents the Cauchy – Pompeiu’s Operator.